Answer :

⇒ bx + ay = 2ab (Multiplying both sides by ab)

⇒ bx + ay - 2ab = 0

ax - by - (a^{2} - b^{2}) = 0

To solve the equation by cross multiplication method, we use:

Putting the values, we get:

So, and

⇒ x = a and y = b

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Let us solvWest Bengal Mathematics

Let us solvWest Bengal Mathematics

Let us write the West Bengal Mathematics

Let us draw the gWest Bengal Mathematics

Let us draw the gWest Bengal Mathematics

Let us draw the gWest Bengal Mathematics

Let us draw the gWest Bengal Mathematics

Let us form the sWest Bengal Mathematics

Let us express thWest Bengal Mathematics

Let us solvWest Bengal Mathematics